사람중심 기업가정신과 기업가적 리더십이 중소기업의 혁신활동과 기업성과에 미치는 영향 - 한수진(Soo Jin Han) (대한경영학회지, 2023)
그간의 기업가정신 연구가 사업성장에 초점이 맞춰졌다면, 기업의 지속적 성장과 경쟁력 확보를 위해서는 사람을중시하는 기업가정신, 즉 사람중심 기업가정신에 대한 연구가 요구된다. 창업기업을 포함한 중소기업의 발전과성과 달성을 위해서는 경영진의 기업가적 리더십을 통한 직원들의 혁신활동을 이끌어내야 한다. 중소기업의 경우기존자원의 효율적 활용을 기반으로 하는 활용적 혁신과 외부자원의 활용과 관련된 탐험적 혁신을 동시에 추구하는양면적 혁신활동이 기업성과에 영향을 미친다. 그러나 사람중심 기업가정신과 기업가적 리더십, 혁신활동과중소기업의 성과에 미치는 영향을 통합적으로 분석한 실증연구는 부족하다. 이에 본 연구는 중소기업 경영진의 사람중심 기업가정신과 기업가적 리더십이 양면적 혁신활동, 즉 활용적혁신활동과 탐험적 혁신활동에 미치는 영향을 각각 분석하였다. 또한 중소기업의 양면적 혁신활동이 기업성과, 즉 재무적 성과와 비재무적 성과에 어떠한 영향을 미치는지를 분석하였다. 마지막으로 사람중심 기업가정신과기업가적 리더십이 기업성과에 미치는 영향을 분석함으로써 중소기업 경영진이나 정책 담당자를 위한 시사점을도출하고자 탐색적 연구를 시도하였다. 본 연구를 위해 서울 및 경기지역 중소기업에 종사하는 200명으로부터수집한 설문조사 데이터를 이용하여 잠재변수들 간의 관계를 측정하기 위해 Smart PLS 2.0를 이용하여 분석하였다. 분석결과에 따르면 사람중심 기업가정신은 양면적 혁신활동의 각각에 유의한 영향을 미치는 것으로 확인되었다. 기업가적 리더십은 양면적 혁신활동 중 활용적 혁신활동에는 정(+) 영향을 미쳤으나 탐험적 혁신에는 유의한 영향을미치지 않는 것으로 확인되었다. 양면적 혁신활동과 기업성과 간의 관계에서 활용적 혁신활동은 기업성과 중재무성과와 비재무성과에 모두 정(+)의 영향을 미쳤다. 탐험적 혁신활동은 기업성과 중 재무성과에는 유의한 영향을미치지 않았으며, 비재무성과에는 유의한 영향을 미치는 것으로 확인되었다. 마지막으로 사람중심 기업가정신과기업가적 리더십 모두 각각 기업성과에 유의한 영향을 미치는 것으로 확인되었다. 위와 같은 연구결과를 바탕으로 중소기업 경영에 관한 시사점과 연구의 한계를 제시하였다. The research on entrepreneurship has focused on business growth, humane entrepreneurship that values people is required to make sure of continuous growth and competitiveness of companies. In order to achieve the development and achievement of small and medium-sized enterprises, including start-ups, it is necessary to lead employees’ innovative activities through entrepreneurial leadership of management. In the case of SMEs, ambidextrous innovation activities that simultaneously pursue exploitative innovation based on the efficient use of existing resources and explorative innovation related to the use of external resources affect corporate performance. However, there is a lack of empirical research that comprehensively analyzes the impact of humane entrepreneurship, entrepreneurial leadership and ambidextrous innovation activities, and the performance of small and medium-sized enterprises. Accordingly, this study analyzed the impact of humane entrepreneurship and entrepreneurial leadership of SME management on ambidextrous innovation that is exploitative innovation activities and explorative innovation activities, respectively. It also analyzed how ambidextrous innovation activities of SMEs affect corporate performance that is financial and non-financial performance. For this study, Smart PLS 2.0 was used to measure the relationship between potential variables using survey data collected from 200 people working in small and medium-sized enterprises in Seoul and Gyeonggi Province. According to the results of this research, it was confirmed that humane entrepreneurship has a significant effect on each of exploitative and explorative innovation activities. It was reported that entrepreneurial leadership had a significant effect on exploitative innovation activities, but did not significantly affect explorative innovation. In the relationship between ambidextrous innovation activities and corporate performance, exploitative innovation activities had a significant effect on both financial and non-financial performance among corporate performance. And explorative innovation activities had not a significant effect on financial performance, but did have a significant effect on non-financial performance. It was reported that both humane entrepreneurship and entrepreneurial leadership had a significant effect on corporate performance, respectively. Based on the above research results, implications and limitations of research on the management of small and medium-sized enterprises were presented as follows. By analyzing the impact of humane entrepreneurship and entrepreneurial leadership on innovation activities, it was confirmed that small and medium-sized companies should regard human capital as a source of innovation. And with this empirical analysis on the relationship between entrepreneurial leadership and ambidextrous innovation activities, the importance of the role of entrepreneurial leaders required in organizational and personnel management of SMEs was identified. In particular, it was confirmed that more systematic approach is needed in establishing strategies such as utilizing external resources, as entrepreneurial leadership does not significantly affect on explorative innovation activities and explorative innovation activities does not significantly affect on financial performance of enterprises. In the case of ambidextrous innovation activities, a study(Siggelkow & Levinthal, 2003) that sequentially pursuing exploitative and explorative innovation is appropriate for corporate success, and companies that pursue both innovation activities at the same time perform better (Benner & Tushman, 2003; Piao, 2010), which also shows different research results. Therefore, in future studies, it is understood that more meaningful implications for each industry can be derived if the industry subject to the survey is further subdivided and studied. KCI Citation Count: 8